Muscle tissue adaptations of high-altitude natives to training in chronic hypoxia or acute normoxia - Desplanches, D; Hoppeler, H; Tuscher, L; Mayet, M. H; Spielvogel, H; Ferretti, G; Kayser, B; Leuenberger, M; Grunenfelder, A; Favier, R (Journal of applied physiology (1985), 1996)
D. Desplanches, H. Hoppeler, L. Tüscher, M. H. Mayet, H. Spielvogel, G. Ferretti, B. Kayser, M. Leuenberger, A. Grünenfelder, and R. Favier Unité Mixte de Recherche 5578 Centre National de la Recherche Scientifique, Laboratoire de Physiologie, Faculté de Médecine, F-69373 Lyon cedex 08, France; Anatomisches Institut, Universität Bern, CH-3000 Bern; Departement de Physiology, Centre Médical Universitaire, 1211 Geneva 4, Switzerland; and Instituto Boliviano de Biologia de Altura, Casilla 717 La Paz, Bolivia Received 26 December 1995; accepted in final form 17 July 1996. Desplanches, D., H. Hoppeler, L. Tüscher, M. H. Mayet, H. Spielvogel, G. Ferretti, B. Kayser, M. Leuenberger, A. Grünenfelder, and R. Favier. Muscle tissue adaptations of high-altitude natives to training in chronic hypoxia or acute normoxia. J. Appl. Physiol. 81(5): 1946-1951, 1996. Twenty healthy high-altitude natives, residents of La Paz, Bolivia (3,600 m), participated in 6 wk of endurance exercise training on bicycle ergometers, 5 times/wk, 30 min/session, as previously described in normoxia-trained sea-level natives (H. Hoppeler, H. Howald, K. E. Conley, S. L. Lindstedt, H. Claassen, P. Vock, and E. R. Weibel. J. Appl. Physiol. 59: 320-327, 1985). A first group of 10 subjects was trained in chronic hypoxia (HT; barometric pressure = 500 mmHg; inspired O 2 fraction = 0.209); a second group of 10 subjects was trained in acute normoxia (NT; barometric pressure = 500 mmHg; inspired O 2 fraction = 0.314). The workloads were adjusted to ~70% of peak O 2 consumption ( O 2 peak ) measured either in hypoxia for the HT group or in normoxia for the NT group. O 2 peak determination and biopsies of the vastus lateralis muscle were taken before and after the training program. O 2 peak in the HT group was increased (14%) in a way similar to that in NT sea-level natives with the same protocol. Moreover, O 2 peak in the NT group was not further increased by additional O 2 delivery during the training session. HT or NT induced similar increases in muscle capillary-to-fiber ratio (26%) and capillary density (19%) as well as in the volume density of total mitochondria and citrate synthase activity (45%). It is concluded that high-altitude natives have a reduced capillarity and muscle tissue oxidative capacity; however, their training response is similar to that of sea-level residents, independent of whether training is carried out in hypobaric hypoxia or hypobaric normoxia. muscle stereology; histochemistry; enzyme activities 0161-7567/96 $5.00 Copyright © 1996 the American Physiological Society